Seasonality in Human Interest in Berry Plants Detection by Google Trends - Kotani, Ayumi; Shin, Nagai; Tei, Shunsuke; Makarov, Andrey; Gavrilyeva, Tuyara (Frontiers in Forests and Global Change, 2021)
The phenology of berry-producing plants, particularly their harvest season, is of human interest and also reflects the ecosystem’s response to the changing environment. We investigated the seasonal dynamics of public interest in berries in boreal ecosystems, mainly in Russia, based on internet search data via Google Trends. There is a typical and culture-specific pattern of seasonal variations in search volume concerning berries across Russia, Finland, and Canada. Generally, the seasonal peak of search corresponds to the common berry harvest season across these countries. We assessed the potential for detecting ecological factors from the social data, in which physical phenomena and socio-cultural aspects are fundamentally superimposed, and discuss its applicability to forest studies.